In-house Shrines in Japanese Corporations and their Background - Nobumichi WATAHIKI; Luiza GATAN; Cristian VLAD; Nitin HINGARH; Saddam IQBAL (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene)
This paper illustrates the tradition of displaying an in-house shrine (kamidana) at Japanese organizations, focusing on the roles of spirituality and purpose in Japanese traditional organizations. The paper further describes how Japanese organizations and employees value tradition, spiritual connections with their legacy business while trying to innovate on products and services, transform business models, operations and revamp strategy.